A simple, fast and inexpensive method to assess salt stress tolerance of aerial plant part: Investigations in the mandarin group - Ben Yahmed, Jihene; de Oliveira, Tahise M.; Novillo, Pedro; Quinones, Ana; Forner-Giner, María A.; Salvador, Alejandra; Froelicher, Yann; Ben Mimoun, Mehdi; Talón, Manuel; Ollitrault, Patrick; Morillon, Raphael (2017)
For grafted plants, salt stress tolerance of the aerial plant part is poorly documented. Thus, we developed a simple, fast and inexpensive method to identify tolerant genotypes. Twigs of 14 mandarin accessions that we previously analyzed as seedlings were cut in solution to prevent embolism and were then evaluated in salt stress condition for a week. Physiological parameters such as gas exchanges, leaf Cl- and Na+, as well as the presence of H2O2 and the activity of enzymes involved in ROS synthesis and detoxification processes were analyzed. One accession known to be tolerant as rootstock was shown to be sensitive with limited Cl- translocation from the solution to the shoot while sensitive accessions when grown as seedlings presented limited wilting symptoms and accumulated large leaf Cl- content. A model is proposed to explain the different strategies of the plant to cope with high toxic ion content. This method allows separation of the root compartment, where ion exclusion mechanisms may exist and have an impact on the salt stress tolerance of the whole plant.